2018
DOI: 10.1073/pnas.1714254115
|View full text |Cite
|
Sign up to set email alerts
|

A randomized controlled design reveals barriers to citizenship for low-income immigrants

Abstract: SignificanceWe provide a randomized test of policy interventions that address barriers to naturalization for low-income immigrants. We find that offering fee vouchers doubles the naturalization application rate among low-income immigrants, but nudges often used by service providers did not increase applications among fee waiver-eligible immigrants below the poverty level. Our results help guide policy efforts to address the problem of low naturalization rates. The current high fees prevent a considerable share… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
38
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
3
1

Relationship

2
6

Authors

Journals

citations
Cited by 42 publications
(41 citation statements)
references
References 19 publications
3
38
0
Order By: Relevance
“…The standardization makes it easier to access the fee waiver and could thereby enable more low-income immigrants to naturalize who could not otherwise afford the application fee. This would be consistent with previous research showing that the current application fee is a barrier to naturalization (13,14).…”
Section: Economic Sciencessupporting
confidence: 93%
See 2 more Smart Citations
“…The standardization makes it easier to access the fee waiver and could thereby enable more low-income immigrants to naturalize who could not otherwise afford the application fee. This would be consistent with previous research showing that the current application fee is a barrier to naturalization (13,14).…”
Section: Economic Sciencessupporting
confidence: 93%
“…More broadly, our results are consistent with findings from the small, but growing, literature examining the returns to policy interventions designed to lower barriers to naturalization among low-income immigrants. Previous work has demonstrated that fee vouchers and an information nudge result in substantial increases in citizenship-application rates (14,15). Here, we find similar, albeit smaller, increases from a related federal intervention that improved access to the fee waiver through the introduction of a standardized form and clear rules for eligibility.…”
Section: Discussionsupporting
confidence: 77%
See 1 more Smart Citation
“…These returns not only benefit immigrants themselves; they also can strengthen host communities by increasing tax revenues and lowering welfare spending. While our study advances understandings of the causal effects of citizenship, more work is necessary to identify its benefits in other contexts and to evaluate the impact of lowering barriers to citizenship, such as lengthy residency requirements or naturalization fees (34). Placebo test shows no significant differences in earnings between immigrants who barley won or lost their citizenship referendum in the last five years before the referendum (N=1,340).…”
Section: Fig 1 About Herementioning
confidence: 91%
“…A few scholars have been able to quantify the importance of specific promotional measures and practical obstacles like fees (e.g. Felix et al, 2008, Hainmueller and Hangartner, 2013, Pastor et al, 2013and Hainmueller et al, 2018.…”
Section: Determinants Of Nationality Acquisitionmentioning
confidence: 99%